A Review of Attempts to Improve Cow Fertility Through Reproductive Management: Estrous Synchronisation - A Elmetwally Mohammed; Hussien Adel; Sharawy Heba; Mostagir Amira; Risha Engy; Eldomany Wael; O Hegab Abdelrouf; H Darwish Madeha; M Zaabel Samy (Journal of Veterinary Healthcare, 2021)
This review focused on the various methods for controlling estrous cycles in well-managed dairy cows. Because up to 70% of dairy cows may stay non-pregnant after an AI procedure, an effective approach for identifying and reinseminating open cows is essential for dairy herds to achieve optimal reproductive performance. Overall, well-managed dairy farms with effective estrus detection programs inseminate 50% or more of non-pregnant cows after behavioral estrus is detected. Cows not detected in estrus are admitted in a resynchronization of ovulation procedure to receive a timed AI (TAI) service to avoid a long interbreeding interval. In Egypt, a widely used program involves starting the Ovsynch protocol (GnRH-7 d-PGF2-56 h-GnRH-16 to 20 h-TAI) 32 days after an initial AI, regardless of pregnancy status. Previous studies have proven that there was no difference in pregnancy/artificial insemination (P/AI) between Ovsynch+P4 and Presynch-Ovsynch, both protocols were equally effective in improving the fertility of cows with a CL 15 mm. The review also addressed different methods for synchronization of ovulation and different factors affecting the selection of the management program.
Keywords: Dairy cows